2022
DOI: 10.1111/jch.14448
|View full text |Cite
|
Sign up to set email alerts
|

Brachial‐ankle pulse wave velocity as a measurement for increased carotid intima‐media thickness: A comparison with carotid‐femoral pulse wave velocity in a Chinese community‐based cohort

Abstract: Carotid-femoral pulse wave velocity (cfPWV) and brachial-ankle pulse wave velocity (baPWV) act as two most frequently applied indicators to evaluate arterial stiffness. Limited studies have systematically compared the relationships between cfPWV/baPWV and increased carotid intima-media thickness (cIMT). This study aimed to investigate the associations of the two PWV indices with cIMT in a Chinese community-based population. A total of 6026 Chinese participants from an atherosclerosis cohort were included in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Our study demonstrated similar results that cfPWC and baPWV were independently associated with the presence of carotid plaque. Our further analysis observed the similar results of relationships between PWV indices and carotid plaque area 38 and increased cIMT 39 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study demonstrated similar results that cfPWC and baPWV were independently associated with the presence of carotid plaque. Our further analysis observed the similar results of relationships between PWV indices and carotid plaque area 38 and increased cIMT 39 …”
Section: Discussionsupporting
confidence: 83%
“…Our further analysis observed the similar results of relationships between PWV indices and carotid plaque area 38 and increased cIMT. 39 …”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the baPWV measurement is known to be simple and reliable for determining arterial stiffness [22]. Arterial stiffness, as measured by baPWV, was associated with the risk of developing diabetes [23].…”
Section: Discussionmentioning
confidence: 81%
“…[29][30][31] Our team has previously conducted long-term studies in the Pingguoyuan and Gucheng communities of Shijingshan District, Beijing, China. 15,32,33 BaPWV and cfPWV were measured in 2018 in this population. In this study, we used the China-PAR model to assess the 10-year ASCVD risk of the subjects as the endpoint to evaluate the relationship between the two types of PWV and the prognosis of ASCVD in this community population of northern China.…”
Section: Discussionmentioning
confidence: 97%
“…Our team has previously conducted long‐term studies in the Pingguoyuan and Gucheng communities of Shijingshan District, Beijing, China 15,32,33 . BaPWV and cfPWV were measured in 2018 in this population.…”
Section: Discussionmentioning
confidence: 99%